Bonus Skills: Examining the Effect of an Unconditional Cash Transfer on Child Human Capital Formation - Jason Gaitz; Stefanie Schurer (Institute of Labor Economics (IZA), 2017)
This paper evaluates the impact of the Australian Baby Bonus a 3000 one-off cash transfer on various aspects of child human capital development. Using high-quality longitudinal cohort data and difference-in-difference models, we compare the outcomes of cohort members whose younger sibling was born marginally on either side of July 1, 2004, when the Baby Bonus was introduced. Our results suggest that the Baby Bonus was not effective in boosting learning, socio-emotional or physical health outcomes of the average pre-school child. This finding is strengthened by the observation that the Baby Bonus did not impact parental well-being, parental behavior and labor supply, the potential mechanisms via which the cash transfer could have affected human capital formation. The muted effect for the Baby Bonus in comparison to significant effects for similar cash handouts in other countries may be explained by its non-targeted and one-off structure. We conclude that the large financial cost of 3000 per child is not justified as an intervention for the entire population to boost children's skills.
Keywords: J24; H53; 330; cash transfers; Baby Bonus; cognitive and non-cognitive skills; health; LSAC